Intra-operative blink reflex neurophysiological monitoring in posterior skull base neurosurgery - Michael W. Y. Lee; Shu-wah Chau (Frontiers in Surgery, 2025)
ObjectivesTo enhance surgical safety with frequent intra-operative neuro-monitoring (IONM) of the blink reflex (BR) in posterior skull base neurosurgery.BackgroundThere are reports stating the potential of facial nerve function preservation using BR IONM but none stating that it helps to protect corneal sensation and vision.MethodsA prospective cohort of 42 consecutive patients with lesions in proximity to the brainstem was operated between January 2021 and April 2024. BR, which is considered the electronic equivalent of the corneal reflex, is elicited by electrical stimulation of the supraorbital nerves. Recording electrodes for R1 responses are placed over orbicularis oculi muscle at the lower eyelid. BR signal loss or an amplitude drop by half or more in R1 from the baseline is regarded as a significant change in BR response. Pre-operative tumour volume and maximal midline shift (MLS) of the brainstem are measured, using readily identifiable anatomical landmarks, namely cerebral aqueduct, median sulcus of the fourth ventricle, and mid-point of interpeduncular fossa. Patients' intra-operative findings and post-operative clinical outcomes are correlated and reported.ResultsBR IONM has a very high accuracy rate (96.7%) in predicting post-operative corneal complications, but can only be successfully done in 30 out of 42 patients (71.4%). There were 17 female and 13 male patients, with age ranging from 41 to 81 (mean 62.0). Ten underwent microvascular decompression and 20 had excision of tumours of size ranging from 1.1 to 81.6 cm3 (mean 21.6 cm3). For the tumour cases, Mann-Whitney U test for unpaired data showed statistically significant difference in tumour volume (p = 0.0016; 37.8 vs. 13.0 cm3) and maximal MLS of the brainstem (p = 0.0271; 8.1 vs. 4.8 mm) regarding the significant change in BR response. This suggests that BR change is a good sentinel indicator of how much brainstem neural tissue is mechanically stretched during excision of the tumour.ConclusionsFrequent IONM of BR is feasible, safe, and useful in the preservation of corneal sensation, especially for patients with large posterior fossa tumours and a distorted brainstem. For patients with the significant change in BR response, prompt referral to the ophthalmologist is useful for the prevention of keratitis and corneal ulceration.